Jogátvétel vagy modellkövetés? : A korlátolt felelősségű társaság megjelenése a magyar jogban - Bujtár, Zsolt (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
The limited liability company was receipted into Hungarian law in 1930. The forty-year delay following the appearance of the German GmbH brought several advantages for Hungarian company law, the legislator created a well thought-out, practical law that also met the long-term needs of the Hungarian economy and the economic actors. Based on the early debates and the first draft of Dávid Pap and its critique by Géza Bozóky, the author examines the new form of company that started as a similar form of a general partnership, which was then considered by Géza Bozóky as a variant of the joint-stock company form. The paper describes the stages and characteristics of the development of this approach in the mirror of the German (1892) and the Austrian (1906) GmbH Acts.